Kualitas Pelayanan Terpadu Pada Penyelenggaraan Mal Pelayanan Publik Kota Sidoarjo - Saptaningtyas Dwi Pertiwi; Indah Murti (Lembaga Pengembangan Kinerja Dosen, 2024)
In general, everyone needs service, in fact, it can usually be said that service cannot be separated from human life. According to Moenir (2002: 6). A service is an activity provided by an intangible group or individual that cannot be owned by a consumer, that is, someone who benefits from the activities of the organization providing the service. According to Dwiyanto (2005: 141) said: